Error estimation by using symmetrization and efficient implementation scheme for 3-stage Gauss method - Sara Syahrunnisaa Mustapha (Tanjong Malim, 2021)
Error estimation by using symmetrization and efficient implementation scheme for 3-stage Gauss method by Sara Syahrunnisaa Mustapha